2016
DOI: 10.1007/s13402-016-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

HPIP promotes epithelial-mesenchymal transition and cisplatin resistance in ovarian cancer cells through PI3K/AKT pathway activation

Abstract: From these results we conclude that HPIP expression is associated with high-grade ovarian tumors and may promote their migration, invasion and EMT, a process that is associated with metastasis. In addition, we conclude that HPIP may serve as a potential therapeutic target for cisplatin resistant ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 56 publications
1
36
1
Order By: Relevance
“…The PI3K/AKT pathway is a potential target for therapeutic intervention due to its pivotal role in the regulation of proliferation, survival, and invasiveness of OC [23]. Hematopoietic PBX-interacting protein promoted the migration, invasion, and EMT in OAW42 cells via activation of the PI3K/AKT pathway by directly interacting with PI3K [24]. He et al [25] revealed that exendin-4 inhibit cell growth, migration, and invasion and enhanced apoptosis by inhibiting the PI3K/AKT pathway during OC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is a potential target for therapeutic intervention due to its pivotal role in the regulation of proliferation, survival, and invasiveness of OC [23]. Hematopoietic PBX-interacting protein promoted the migration, invasion, and EMT in OAW42 cells via activation of the PI3K/AKT pathway by directly interacting with PI3K [24]. He et al [25] revealed that exendin-4 inhibit cell growth, migration, and invasion and enhanced apoptosis by inhibiting the PI3K/AKT pathway during OC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Herein we proposed that NID1 exacerbated resistance of ovarian cancer cells via upregulating the expression of MDR1 and ABCG2 (Figure 8E and Figure 8G), two well-known ABC transporters. Besides NID1, several regulators, such as HPIP, NANOG and FOXM1, have been reported to promote EMT of ovarian cancer cells and then confer them drug resistance, involving PI3K/AKT pathway, STAT3 pathway, etc [3336]. The aforementioned results implicated that NID1-overexpressed ovarian cancer cells potentially exhibited cancer stem cell-like characteristics which imparts the metastatic and chemoresistant advantage to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that microRNAs (miRNAs) are involved in the process of epithelial-mesenchymal transition (EMT) in various types of cancer (3)(4)(5)(6), and various studies have revealed that the EMT may be associated with the drug resistance of cancer cells (7)(8)(9)(10). Furthermore, by comparing the miRNA expression profiles between breast cancer cell lines in our previous study, we determined that the expression of miR-93 was increased markedly in drug-resistant MCF-7/AdrVp cells compared with the parental MCF-7 cell line (11).…”
Section: Introductionmentioning
confidence: 99%